Kemampuan Menulis Cerpen Melalui Pembelajaran Berbasis Multimedia pada Siswa Kelas VII E SMP Negeri 3 Kupang Tahun Pelajaran 2025/2026 - Realita Helianak; Ronni M. Ndun; John Darwis Fallo; Ona Diana Bani (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe students' ability in writing short stories through multimedia-based learning. This study employs a descriptive method with a quantitative and qualitative approach. Data collection techniques were carried out through the assignment of writing short stories, which were then analyzed based on scoring guidelines covering four assessment aspects, namely the content aspect of the short story, the structure aspect of the short story, the linguistic aspect, and the creativity aspect. The subjects of this study were 30 students of SMP Negeri 3 Kupang, specifically seventh-grade E students, consisting of 16 males and 14 females. The results of this study indicate that students' ability in writing short stories through multimedia-based learning is still varied. In the content aspect of the short story, some students have been able to align the theme with the story's content, but there are still those who are lacking in connecting the theme with the story's content. In the structure aspect of the short story, most students have been able to write stories according to the short story structure, but there are still several students who pay less attention to the short story structure in their writing. In the linguistic aspect, some students have been precise in using vocabulary and formal language, but there are several students who still use everyday language. Meanwhile, in the creativity aspect, some students have been able to create stories well, although there are several aspects that still need to be improved. In terms of percentages, students who obtained a score in the very capable category amounted to 14 students (46.67%), students in the capable category amounted to 9 students (30.00%), and students in the fairly capable category amounted to 7 students (23.33%). The final average score they obtained was 80.6. Thus, the ability to write short stories through multimedia-based learning among seventh-grade E students of SMP Negeri 3 Kupang falls into the capable category.